Desenvolvimento de um novo sistema dinâmico para avaliação da liberação de fármacos - Cinman, José Luiz Ferreira [UNESP] (2014)
Drug delivery systems have become important in the field of pharmacology and biomedicine, as they may reduce the therapeutic dose through the local release, avoiding possible effects during its passage through the body. Biomembranes made of natural latex extracted from Hevea brasiliensis has shown interesting results in biomedicine, by presenting proteins that stimulate angiogenesis, wound healing, constitute prostheses and good performance as a matrix for release of drugs, plant extracts, nanoparticles and proteins. This paper presents the development and use of a new system, said dynamic, where the release occurs from circulating fluid and using natural latex biomembranes as carrier for the releases. In order to supplement its healing properties, ketoprofenwas chosen as model drug because of its anti-inflammatory, analgesic and antipyretic properties, in the veterinary and human use. Biomembranes were produced by mixing natural rubber latex with a ketoprofen solution by the casting, and dried at room temperature. A new dynamic system for drug delivery with circulating flow was implemented and the static (no flow) and dynamic releases were compared in order to obtain the influence of the flow in the release. The biomembranes were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and mechanical testing. The SEM results showed the existence of the drug in the surface membranes. The FTIR results showed that there is no interaction between the drug and biomaterial, although the incorporation of ketoprofen makes the biomembranes more fragile by reducing the Young's modulus, elongation at break and tensile strength, indicating that the drug is only interleaved in the matrix polymer. These results indicate differences between static and dynamic release, since the dynamic released 30% more drug than static. Mathematical modeling showed that the initial release...